Dam Break Analysis of Batu Dam using Hec-Ras - S. I. N. S. Hashim,; Abu Talib, Siti Hidayah; M. S. Abustan,; E. A. K. A. E. Mohamed,; Z. Muhammad, (International Journal of Integrated Engineering, 2024)
Dam is commonly built in Malaysia as it provides benefits to the local population, mainly agricultural activity and flood control measures. However, its massive potential energy reservoir would impose risk of sudden containment breach leading to loss of life and property at inhabited downstream area. Simulations of dam break events are crucial to characterizing and reducing threats due to potential dam failures. In all post-event natural disasters, where most structural countermeasures have been lost, the preparation of a smoother evacuation mechanism remains the most critical prevention tool for successful evacuation planning. The urgency of designing an appropriate emergency planning is important in response to the disaster. To perform a dam break analysis, hydraulic modeling is required, which involves routing the inflow flood through a reservoir, estimating dam breach characteristics, and downstream routing/modeling issues. The HEC-RAS (River Analysis System) software is commonly used for dam break studies. The software provides information on how to perform a dam break analysis, including the unique hydraulic modeling aspects that are required. Batu dam has the highest percentage of the population at risk (PAR) and most likely exposed to the flood disaster due to dam break. From flood boundary maps, it was estimated that 78% of residential areas would be affected if a dam break disaster occurs. From the simulation, the maximum depth can reach up to 18m with an estimated flow speed between 0.2 – 3m/s. At these depth and flow speed, people may lose strength and unable to control themselves in flood and would cause death and injury. Flood arrival time took 15 to 22 hours for flooding to arrive downstream with a maximum flood depth of 5.07m at Persiaran Jasa Utama and the highest depth of 12.62m at Kampung Baru Batu Caves with flood velocity between 1.60m/s to 1.46m/s. Analysis and simulation of embankment dam breach events and the resulting floods are crucial for distinguishing and mitigating dangers from potential dam failures. Accurate forecast of inundation levels and the time of flood wave arrival at downstream key places is required for the development of effective emergency response plans.